Evaluation of Curriculum Implementation in Nigeria Universities – A Feasibility Study - Nwosu , John N.; Odachi , Gabriel N. (African Journal of Education,Science and Technology (AJEST), 2017)
This research investigated the use of lecture material by students in the preparation of lectures and examination. The instigation includes determining if departmental handbook which contains the curriculum that students in the department are to offer before their graduation are made available to students at the point of their registration in the department. It also includes determining if there is a need to evaluate lecture materials given by lecturers to students to know if it compliances with minimum benchmark established by National University Commission (NUC). The research involved administering structured questionnaire to 200 students selected randomly from University of Nigeria, Nsukka and Chukwuemeka Odimegwu Ojukwu University, Uli to elicit response on the use of lecture materials. Chi square was used to analyze the data collected from the respondents. The mean of the nominal value is equal to 2.5 at 0.005 level of confidence and 12 degree of freedom. The calculated x2 of 207.6 exceeds the x2 critical value of 21.0. This shows that students use lecture material in the preparation of lectures and examination. The result also shows that students are aware of departmental handbook which was developed in line with NUC curriculum. Also the research reveals that there is a need to evaluate the lecture materials given to students to know it it compliance with NUC minimum benchmark.